2022
DOI: 10.14336/ad.2021.1027
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Renal Fibrosis

Abstract: Renal fibrosis is a common process of almost all the chronic kidney diseases progressing to end-stage kidney disease. As a highly conserved lysosomal protein degradation pathway, autophagy is responsible for degrading protein aggregates, damaged organelles, or invading pathogens to maintain intracellular homeostasis. Growing evidence reveals that autophagy is involved in the progression of renal fibrosis, both in the tubulointerstitial compartment and in the glomeruli. Nevertheless, the specific role of autoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 185 publications
(209 reference statements)
1
18
0
1
Order By: Relevance
“…Activation of autophagy protects kidney cells under stress, while lack of autophagy increases kidney susceptibility to injury, leading to impaired renal function and accumulation of damaged mitochondria, which in turn leads to more severe renal fibrosis. However, other studies have found that persistent activation of autophagy is detrimental after severe renal injury, leading to renal cell senescence and promoting renal fibrosis by secreting pro-fibrotic cytokines (Liang et al, 2022). Therefore, maintaining the balance of autophagy is crucial for improving renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of autophagy protects kidney cells under stress, while lack of autophagy increases kidney susceptibility to injury, leading to impaired renal function and accumulation of damaged mitochondria, which in turn leads to more severe renal fibrosis. However, other studies have found that persistent activation of autophagy is detrimental after severe renal injury, leading to renal cell senescence and promoting renal fibrosis by secreting pro-fibrotic cytokines (Liang et al, 2022). Therefore, maintaining the balance of autophagy is crucial for improving renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is closely related to renal fibrosis, and a recent study found that sustained activation of autophagy is detrimental to the kidney after severe injury, leading to renal cell senescence and promoting renal fibrosis through the secretion of pro-fibrotic cytokines (Zheng et al, 2019). mTOR is one of the key regulators of autophagy in mammalian cells and can be activated by signal transducers including PI3K and Akt activation in response to insulin, IGF and other growth signals, which in turn inhibit autophagy (Liang et al, 2022). And further studies have shown that IGF-1, as a PI3K/Akt activator, improves renal fibrosis indicators in UUO rats (Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As the common final pathway of nearly all chronic and progressive kidney diseases to progress to end-stage renal failure, renal fibrosis refers to the accumulation of ECM in the renal parenchyma, which affects about 10% of the global population ( 90 92 ). The main function of the mammalian kidney is to keep the water, electrolyte, and acid-base balance of the body, while meanwhile excreting metabolic waste from the body.…”
Section: Macrophage Autophagy In Organ Fibrosismentioning
confidence: 99%
“…When kidney cells are exposed to oxidative stress and ER stress, autophagy activation plays a vital role in cell survival [ 31 ]. Autophagy also participates in the intracellular degradation of collagen, prevents the continuous accumulation of ECM, and plays a crucial role in inhibiting renal fibrosis [ 32 ]. Autophagy is mainly regulated by the mechanistic target of rapamycin (mTOR) signaling pathway, and its upstream is managed by AMP-activated protein kinase (AMPK).…”
Section: Signaling Pathways For Dkd Progressionmentioning
confidence: 99%